2021
DOI: 10.46328/ijemst.1550
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Handbook on Multimedia Integration in Mathematics Teaching for Indonesian Primary School Students

Abstract: This study has developed a digital mathematics handbook that helps students to strengthen their mathematical skills at the elementary level of education. A survey of mathematics teachers collected data. In developing an integration manual on technology based on a survey of the state of technological integration in schools, it employed a research and development (RD) approach. A number of 24 teachers participated in the material creation. The multimedia materials produced during the trial were developed and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Multimedia computers can help students learn the piano more effectively by combining video and audio elements. It is also possible to learn more thoroughly by interacting with the computer and the pupils [11][12][13][14][15]. erefore, Internet of ings technology and multimedia technology have become an indispensable part of modern piano intelligent teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Multimedia computers can help students learn the piano more effectively by combining video and audio elements. It is also possible to learn more thoroughly by interacting with the computer and the pupils [11][12][13][14][15]. erefore, Internet of ings technology and multimedia technology have become an indispensable part of modern piano intelligent teaching.…”
Section: Introductionmentioning
confidence: 99%
“…One of which was mathematics books. The previous study done by previous study concluded that the students' learning using the handbook did not show the optimal result (Christenson et al, 2012;Susanto et al, 2021). In addition, the result of the interview and observation performed in SMA N 7 Denpasar showed that there was the same result; namely, the students still had problems understanding the handbook.…”
Section: Introductionmentioning
confidence: 89%
“…Industrial Revolution 4.0 and the 21st century (Warsita, 2018), a teacher must be able to incorporate technology into the learning process in order to make it more engaging for students (Susanto, et al, 2021). Sariyatun, et al, (2018) highlight practical reasons for teachers to utilize digital learning materials, such as the teacher's presumption that digital learning materials are more engaging, simpler to comprehend, and less expensive for students.…”
Section: Coefficient Of Determination (R2)mentioning
confidence: 99%